(untitled) (Research, Society and Development, 2022)
The aim of this article was to demonstrate the development of a collection of exergames for neurological rehabilitation called Therapy Game and System (TGS). At first, a Game Design Document (GDD) was written about all the details ranging from the division of each team member to the mechanics of the games. The electronic game development engine distributed free of charge called UNITY 2018, which uses the C# programming language, was used to implement the entire software concept, and with the help of the Photoshop 2020 program, it was possible to design the graphic layout. For the gameplay, the concept of Human User Interface was used with the use of the Makey Makey device. Six games divided into two collections of three each were elaborated. Both were registered as a computer program in the NIPI. Preliminary tests were made which the games proved to be functional, however, future graphic and gameplay tweaks must be performed. It is a low-cost technology and its development is based on scientific foundations on the subject and refinements of the software itself in order to provide a pleasant and effective experience for patients.